Highly efficient hydrolysis of ammonia borane by anion (−OH, F−, Cl−)-tuned interactions between reactant molecules and CoP nanoparticles. Issue 4 (8th December 2016) - Fu, Zi-Cheng; Xu, Yong; Chan, Sharon Lai-Fung; Wang, Wei-Wei; Li, Fang; Liang, Fei; Chen, Yong; Lin, Zhe-Shuai; Fu, Wen-Fu; Che, Chi-Ming
Abstract : An anion-assisted hydrolytic H2 -releasing ultra-high performance system involving ammonia borane and a CoP nanoparticle catalyst has been established under ambient conditions. Abstract : The CoP nanoparticle catalyst had excellent catalytic activity and a short catalytic induction period in the presence of anions, and high sustainability in ammonia borane hydrolysis, with an initial turnover frequency of 72.2 mol(H2 ) mol(CoP) −1 min −1 at ambient temperature. This value is unprecedented for noble-metal-free catalytic systems.